A New Framework to Estimate the Near-Term Path of the Fed Funds Rate. Issue 4 (October 2016) - Bullard, Sam; Iqbal, Azhar; Silvia, John
Abstract We propose a forward-looking method to estimate the path for the federal funds target rate. We utilize six-month out probabilities of inflationary and disinflationary pressures, along with a labor market index, to estimate the fed funds rate. We further suggest that due to the changing nature of economies and impending risks to the economic outlook, a time-varying method (consistent with the nature of risks) would help decision makers to improve effective decision making. Our econometric results suggest disinflation (or disinflationary pressure), not inflationary pressure, best explains fed funds rate movements from the 1990s forward. Based on June 2016 data, there is a 55 percent chance that the inflation rate would stay below 1.5 percent during the next six months. The recent higher disinflationary pressure probability may be one reason the FOMC has repeatedly lowered its path for the fed funds rate. Unfortunately, the low-inflation zombie is real.